Mortality evolution in Cienfuegos province, 2010-2019 - Yenisvel Yut Vidal; Yadira Sarría Zerquera; Evangelina Dávila Cabo de Villa (Medisur)
Background: the mortality study, as well as its change over time, is of vital importance, since it allows us to capture progress and setbacks in health. Objective: to characterize the behavior of mortality in the Cienfuegos province. Methods: descriptive, cross-sectional study, which had the Cienfuegos entire population as universe, between the years 2010-2019. The analyzed variables were: crude mortality rate, infant mortality rate, specific mortality rate by age, sex, causes of death, maternal mortality rate and notes on life expectancy at birth, as well as all deaths that occurred according to characteristics. . The data were obtained from the National Office of Statistics and Information statistical yearbooks, from the National and Provincial Statistics Directorate of the Public Health Ministry. Results: the crude death rate increased in the last decade by 17.5% and men died more than women. Infant mortality ranged from 2.7 to 5.0 per year. The top three causes of death were heart disease, malignant tumors, and cerebrovascular disease. Of 13 maternal deaths, seven were from direct causes and six were indirect. Conclusions: the crude mortality rate in the province in the period 2010-2019 experienced an increase in its values and with it the causes of death, a behavior that demonstrates the need to combine different factors, whether endogenous or exogenous, to improve the survival capacity of the Cienfuegos population.